Prothrombin and β2-glycoprotein I frequently contribute to antiphospholipid antibody interactions with phospholipids and the generation of abnormal waveform profiles in coagulation assays - Su, Zuowei; Izumi, Tomonori; Ortel, Thomas L. (Thrombosis and Haemostasis, 2003)
Transmittance waveforms are generated during clot formation on photo-optical coagulation analyzers. We previously showed that 61.5% of patients with antiphospholipid antibodies (APLA) exhibited a negative deflection in the pre-coagulation phase of the prothrombin time (PT slope 1). The current studies investigated the ‘molecular basis’ of this abnormal parameter. We found that the negative PT slope 1 is IgG-mediated and is not dependent on the presence of fibrinogen or thrombin activity. We also found that IgG from most of the patients required a specific thromboplastin and the presence of prothrombin or β2-glycoprotein I (β2GPI) to produce an abnormal IgG waveform assay. In addition, the abnormal IgG waveform required cofactor binding to phospholipids when β2GPI was the cofactor, and annexin V could partially block this interaction. In conclusion, these results showed that the interactions of IgG with phospholipids via β2GPI or prothrombin constitute the core mechanisms of the abnormal waveforms.
Keywords: Antiphospholipid antibodies; prothrombin; β2-glycoprotein I; transmittance waveforms